Simulating graphene-based single-electron transistor: incoherent current effects due to the presence of electron-electron interaction - dos Santos, Washington F [UNESP]; Amorim, Felippe [UNESP]; Reily Rocha, Alexandre [UNESP] (IOP Publishing, 2025)
Carbon-based nanostructures have unparalleled electronic properties. At the same time, using an allotrope of carbon as the contacts can yield better device control and reproducibility. In this work, we simulate a single-electron transistor composed of a segment of a graphene nanoribbon coupled to carbon nanotubes electrodes. Using the non-equilibrium Green’s function formalism we atomistically describe the electronic transport properties of the system including electron-electron interactions. Using this methodology we are able to recover experimentally observed phenomena, such as the Coulomb blockade, as well as the corresponding Coulomb diamonds. Furthermore, we separate the different contributions to transport and show that incoherent effects due to the interaction play a crucial role in the transport properties depending on the region of the stability diagram being considered.
Keywords: electron-electron interaction; electronic transport; graphene quantum dots; non-equilibrium Green’s functions